“Solutions” are not the answer - Davies, Todd; Loghmani-Khouzani, Taha; Fath, Brian D. (Frontiers in Sustainability, 2024)
Academics and policy-makers often frame their work by defining "problems" and proposing "solutions". While this approach is effective in closed systems, where problems can be clearly defined, we critique its application to open systems, where such clarity is not possible. We highlight how narrowly framed "solutions" can lead to unintended consequences and policy incoherence when applied to open systems, and advocate for a rhetorical shift from "problems and solutions" to "challenges and responses". This reframing acknowledges the dialectical nature of interacting with open systems and encourages decision-makers to engage in a continuous and evolving praxis, where challenges are addressed iteratively, rather than problems being solved once and for all. We argue that this approach is more realistic, avoiding the pitfalls of short-term solutionism by promoting a more holistic and ongoing engagement with complex, open systems.Regard life not as several isolated problems, but comprehensively, as a whole, with a mind that is not suffocated by the search for solutions. (Krishnamurti 1996, 52